2023
DOI: 10.1039/d3ce00362k
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure induced switching between halogen and hydrogen bonding regimes in 1,4-dioxane iodine monochloride

Abstract: The structure of the complex formed between 1,4 dioxane and iodine monochloride has been studied as a function of pressure using neutron powder diffraction. Initial compression was accompanied by a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…We have previously investigated neutron structural studies of halogen-bonded systems at ambient pressure and, 17–19 more recently, reported one of very few neutron-determined structures under pressure. 20 In this study, we have sought to explore a halogen-bonded system which exhibits a sufficiently flexible geometry such that, under pressure, its bonding environment might encompass much of the known distance parameter space across other CSD-recorded structures—as a ‘representative’ system. We have identified the simple addition compound formed between trimethylamine and I–Cl (hereafter TMA–ICl) as such a structure; earlier work by some of us showed the presence of unexpected C–H⋯Cl interactions, owed to the very different electronegativties associated with the I and Cl halogens.…”
mentioning
confidence: 99%
“…We have previously investigated neutron structural studies of halogen-bonded systems at ambient pressure and, 17–19 more recently, reported one of very few neutron-determined structures under pressure. 20 In this study, we have sought to explore a halogen-bonded system which exhibits a sufficiently flexible geometry such that, under pressure, its bonding environment might encompass much of the known distance parameter space across other CSD-recorded structures—as a ‘representative’ system. We have identified the simple addition compound formed between trimethylamine and I–Cl (hereafter TMA–ICl) as such a structure; earlier work by some of us showed the presence of unexpected C–H⋯Cl interactions, owed to the very different electronegativties associated with the I and Cl halogens.…”
mentioning
confidence: 99%